PENERAPAN MODULASI DPSK PADA TRANSMISI SERAT OPTIK - Yuniarti, Harumi; Cholis, Bambang (Jurnal Teknik Elektro, 2010)
Nowadays the implementions of the transmission modulation techniques (high channel capacity) in optical fibres have been widely developed, one of the successful key factors of this system is the application of digital modulation techniques and the adjustment of modulation pattern. Modulation pattern of adjustment measures on the operational requirements of the system was made possible by the utilization of techniques Apol RZ-DPSK (Alternate Polarization Return-to-Zero Differential Phase Shift Keying). It is considered likely because it can reduce the effects of inter-channel non-linearity, noise and simultaneously demonstrates increasing system margins. Keywords: ASK, FSK, PSK, DPSK, NRZ-DPSK, RZ-DPSK, Apol RZ-DPSK